The Effect of Nutrition Education on Knowledge, Attitudes, and Iron Intake in Adolescent Girls - Zakiah, Sitti; Toaha, Aminah; Abri, Nur; Wahyutri, Endah (Media Publikasi Cendekia Indonesia, 2023)
Anemia in adolescent girls is still a health emergency in developing countries, including Indonesia. This is still a priority scale for health management in various countries because it will harm the generation to be born. The education movement is considered very effective and efficient in preventing problems early. This study aimed to determine the influence of education on the knowledge, attitudes, and iron intake of adolescent girls at Public high schools 1 Tanjung Redeb. The research method is an experimental Quasy with a design of two groups Pre-test and Post-test conducted in May-June 2023. 50 research samples were selected in total sampling. Nutritional status is measured using anthropometric tools, and knowledge, attitudes, and food recalls are obtained using questionnaires that have been validated by tests. Independent sample T-test and Paired T-test and Wilcoxson test. The results showed that there was an effect of nutrition education in the intervention group on increasing knowledge (p 0.000) while the control group did not (p 0.100), while attitude did not affect the intervention and control groups respectively (p 0.876) and (p 0.410). Nutrient intake in the intervention and control groups (p 0.709) and (0.143) respectively. There were differences in knowledge after education in the control and intervention groups (p 0.013). Meanwhile, attitudes and iron intake were no different (p 0.722) and (p 0.100) after intervention and control education.